P038 Sleep disorders, perceived control over sleep and depression in paramedic students. (9th November 2022) - Evans, M; Reynolds, A; Brown, B; Wanstall, S; Crowther, M; Rawson, G; Vakulin, A; Lechat, B; Rayner, T; Eastwood, P; Adams, R
Abstract: Introduction: University students are commonly affected by sleeping difficulties and poor mental health, and ~20% of this demographic live with a clinical sleep disorder. This is particularly concerning for students who will progress into careers which will introduce further sleep disturbance via shift work schedules. The aim of the current study was to explore the relationship between sleep disorders and depression in paramedic students, and determine whether perceived control over sleep moderates the relationship. Methods: Data from fifty-three Flinders University Paramedic students was included, consisting of sleep disorder screening (obstructive sleep apnea, insomnia and restless legs syndrome), and mental health (Patient Health Questionnaire-9) questionnaires. PHQ-9 scores ranged from 0 to 27, with higher scores indicating more severe depression. Regression analysis adjusted for age and sex at birth were conducted using SPSS version 27. Results: Meeting criteria for a sleep disorder (n=21, 38.2%) was associated with higher depression scores (mean+standard error) in paramedic students (for sleep disorders vs no sleep disorders, 11.4±0.9 v 4.3±0.8, F₁, ₅₂=33.5, p <.001). High perceived control over sleep was associated with lower depression scores than low perceived control 5.3±0.9 vs 9.6±1.1, F₁, ₅₂=9.0 p = .004) but no moderating effect was observed (p = 0.17). Discussion: Sleep disorders and low perceived control over sleep are independently associated with higher depression scores. Investigation and management of factors contributing to low perceived control over sleep, together with early screening and management of sleep disorders are important priorities to support paramedic student sleep and mental health prior to commencing shift work.